Trends in treatment of problematic cannabis use in Ontario’s specialized addiction treatment system from 2010/11 to 2015/16: a repeated cross-sectional study of a health administrative database - Imtiaz, Sameer; Kurdyak, Paul; Samokhvalov, Andriy V.; Mobashir, Mahhum Mumtaz; Que, Bill; Elliot, Daniel; Rehm, Jürgen (CMAJ Open, 2018)
Background: Little is known about trends in the treatment of problematic cannabis use in Canada. Trends in treatment utilization for problematic cannabis use were examined, as well as trends in the associated sociodemographic characteristics and frequency of cannabis use.Methods: This was a repeated cross-sectional study using data from the Drug and Alcohol Treatment Information System, capturing utilization of all community funded addiction treatment services in Ontario, Canada. Clients in treatment for their own problematic cannabis use from 2010/11 to 2015/16 were included. Two distinct groups were formed: clients with problematic cannabis use only (the cannabis-only group) and clients with problematic use of cannabis and other substances (the cannabis-plus group). Estimates of the number of clients in each of these groups and their cannabis use frequency (past 30 days) were characterized over time by new admissions and total caseload (new admissions plus carryovers).Results: There were 152 984 admissions for 83 621 clients over the study period. The number of clients with new admissions in the cannabis-only group decreased from 2954 (95% confidence interval [CI] 2848–3062) in 2010/11 to 2342 (95% CI 2248–2439) in 2015/16. Similar downward trends were observed in the number of clients in the total caseload of this group. The number of clients with new admissions in the cannabis-plus group was stable, but the total caseload increased from 20 139 clients (95% CI 19 862–20 419) in 2011/12 to 21 816 (95% CI 21 527–22 107) in 2015/16. Proportions of daily cannabis use increased among clients in both groups.Interpretation: The number of clients in treatment for problematic cannabis use only decreased over the study period, but the frequency of cannabis use increased among clients in both groups. Given the potential reductions in treatment that is unnecessary from a clinical standpoint, alignment of treatment programming with disorder severity may be warranted.